"We're Not Going to Do That Because It's Not Right": Using Pedagogical Responsibility to Reframe the Doublespeak of Fidelity. Issue 1 (April 2016) - Santoro, Doris A.
Abstract: In this essay, Doris Santoro examines the discourse of "fidelity of instruction" to show how it is doublespeak for teacher compliance that is incompatible with democracy and education. Analyzing the distorted use of the term "fidelity" by market‐based reformers, Santoro illustrates how it can be used as a weapon against teacher intelligence and moral response. She argues that John Dewey's philosophy provides conceptual resources to reframe some teacher infidelity as intelligent response, the moral agency required for pedagogical responsibility.